A Preliminary Study on The Speaking Confidence of Non-Formal Learners in Indonesia through TikTok-Based Learning - Difanti Alfina Damayanti; Rozanah Katrina Herda; Sara Wendt (Wahana Pendidikan, 2026)
In the 21st century, education requires learners to develop cognitive knowledge alongside critical thinking, creativity, collaboration, and communication skills, with English serving as a key medium for global interaction and professional growth. Adult learners in non-formal settings, such as a non-formal education institution in Magelang, Indonesia, often face challenges in speaking due to anxiety, limited exposure, low self-efficacy, and competing work–family responsibilities. This descriptive qualitative study aimed to describe classroom conditions and learner participation, identify indicators of speaking confidence, and explore the potential of TikTok from a teacher's perspective. Data were collected through classroom observations and semi-structured interviews, and then analysed thematically. Findings revealed that psychological barriers, teacher-centred instruction, minimal feedback, and contextual fatigue hinder participation and fluency, while TikTok promotes confidence through rehearsal, creativity, peer interaction, and reduced performance pressure. The study concludes that supportive feedback, learner-centred approaches, and careful digital integration can enhance motivation and speaking skills. The implications emphasise the need for emotionally safe learning environments, teacher development in providing constructive feedback, and attention to digital privacy. Future research should employ mixed-methods, longitudinal tracking, and multi-site frameworks to explore how digital platforms and teacher assistance can further enhance speaking confidence in diverse non-formal EFL contexts.